Strategy of Local Government in Increasing The Number of Tourists on Bawean Island - Durratun Nashihah (Jurnal Ilmiah Administrasi Publik, 2022)
Bawean Island has many locations with natural objects with beautiful views. beautiful natural objects are a potential that can attract tourism visits. However, this beautiful natural object has not been maximized, the number of tourists who come to Bawean Island is still less than some other areas in Indonesia. There are several aspects that can attract tourists, including tourist attractions, infrastructure, accessibility, institutions, participation, and hospitality. Therefore it is important for the government to make policies and regulations to assist stakeholders in realizing all aspects of supporting tourism with the aim of increasing the number of tourists on the island of Bawean. While the type of research used in this research is a case study. Case Studies are qualitative strategy in which the researcher explores in depth a program, event, activity, process, or one or more individuals. What is done in this research is to collect and analyze data on regulations and government policies related to tourism, especially from the number of tourist visits. It is hoped that this research will benefit from knowing what policies and plans can be developed in the future to develop the number of tourist visits on the Bawean Island.